2021
DOI: 10.1177/08948453211033903
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autonomy Support and Job Crafting in Interest Incongruence: A Mediated Moderation Model

Abstract: Interest incongruence, or the mismatch between employees’ vocational interests and their work environments, tends to induce negative work attitudes and behaviors among employees. Combining conservation of resources theory and person–environment fit research, we propose a mediated moderation model explaining how autonomy support and job crafting mitigate the detrimental effects of interest incongruence on job satisfaction and absenteeism. Using data collected across two time periods from a sample of 428 Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As described earlier, one mechanism through which individuals may cope with misfit by changing their environment is job crafting (Tims et al, 2013). Given enough autonomy, individuals may actively work to change aspects of their job to help align their work environment with their own attributes (Li et al, 2022). In doing so, individuals may simultaneously engage in active coping strategies that relieve or enhance other stressors.…”
Section: The Multifaceted Role Of Person-environment Fit In the Stres...mentioning
confidence: 99%
“…As described earlier, one mechanism through which individuals may cope with misfit by changing their environment is job crafting (Tims et al, 2013). Given enough autonomy, individuals may actively work to change aspects of their job to help align their work environment with their own attributes (Li et al, 2022). In doing so, individuals may simultaneously engage in active coping strategies that relieve or enhance other stressors.…”
Section: The Multifaceted Role Of Person-environment Fit In the Stres...mentioning
confidence: 99%
“…When employees perceive autonomy support, they can be the agency of their own behaviors and experience satisfaction with self-determination which leads to meaningful work perception (Deci et al, 2017; Gagné & Deci, 2005). In contrast, supervisors’ control forces employees to think and behave in a specific way, which greatly frustrates their psychological needs and stops them from seeking work meaningfulness (Li et al, 2022). In the nursing industry, autonomy support gives nurses the freedom to decide how to achieve their personal goals, enhancing self-realization and then increase their understanding of the meaning of their work in a self-oriented pathway.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…It is widely assumed that positive emotions are a result of P‐E fit (Yu, 2009). In parallel, it was noted that person–job misfit triggered lower positive affect and higher negative affect in employees (Li, Yang, et al., 2022). In addition, previous studies have found that P‐E fit increases the job satisfaction of employees (Li et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research has generally reported results in the expected direction for the employee population, the results are mixed. For instance, the impact of interest incongruence, an indicator of P‐E fit, on job satisfaction was not the same for everyone, and there were significant differences, especially concerning the level of job crafting (Li, Flores, et al., 2022). Job crafting did not impact all employees’ P‐E fit and job satisfaction to the same extent (Li et al., 2023).…”
Section: Introductionmentioning
confidence: 99%